Green maintenance for heritage buildings: Low carbon laterite stones repair appraisal - Kayan, Brit; Halim, Imaduddin Abdul; Mahmud, Nurush Syahadah (Italian Association of Chemical Engineering - AIDIC, 2018)
Sustainability commonly denotes an integration of economic, environmental and societal domains. Low carbon repair of buildings also conforms to these broad domains. Environmental consideration in low carbon repair appraisal for heritage buildings has become increasingly important and this paper supports this expanding area. This paper gives an insight on how 'Green Maintenance' concept and methodology practically determine and ultimately substantiate appraisal on low carbon repair for laterite stones of selected multiple case studies of heritage buildings located at Historical City of Melaka, Malaysia. This paper also provides highlights of comparative study and analysis of these case study buildings on their common techniques and materials for laterite stones repair. This has been achieved through quantification of embodied carbon expenditure expended in laterite stones repair within 'cradle-to-site' boundary of Life Cycle Assessment (LCA) using formulaic expression and calculation procedure of 'Green Maintenance' model. The calculation procedures of the model were adopted to enable evaluation of CO2 emissions in terms of embodied carbon expenditure expended from laterite stones repair for selected case studies during maintenance phase. It is found that stone replacement technique is considered as the most sustainable repair technique, mainly due to its high longevity of repair, in terms of generated Environmental Maintenance Impact (EMI) of Green Maintenance modelling. More importantly, EMI of the model relays the true value of CO2 emissions contextualised within the longevity of repair and minimal intervention that allow low carbon repair appraisal approach.